Preoperative embolization strategy for the combined resection of replaced right hepatic artery in pancreaticoduodenectomy: a small case series - Shintaro Takeuchi; Yoshiyasu Ambo; Yoshihisa Kodama; Minoru Takada; Kentaro Kato; Fumitaka Nakamura; Satoshi Hirano (Surgical Case Reports)
Abstract Background Replaced right hepatic artery (rRHA) is a common vascular variation, and combined resection of this vessel is sometimes needed for the curative resection of pancreatic head malignancy. Safe surgical management has not been established, and there is a small number of reported cases. Here, we reported five cases, wherein preoperative embolization of rRHA was performed for combined resection. Case presentation All patients had pancreatic head malignancies that were in contact with rRHA. We performed a preoperative embolization of the rRHA before the scheduled pancreaticoduodenectomy for the combined resection. Arterial embolization was safely accomplished, and the communicating arcade from the left hepatic artery via the hilar plate was clearly revealed in all cases. Four patients underwent the operative procedure, except for one patient who had liver metastasis at laparotomy. No patient suffered from a severe abnormal liver function during the management; however, one patient had multiple liver infarctions during the postoperative course. Conclusions Preoperative embolization for the combined resection of rRHA in pancreaticoduodenectomy can be a management option for the precise evaluation of hemodynamics after sacrificing rRHA. In our cases, arterial flow to the right liver lobe was supplied by the left hepatic artery via the bypass route, including the communicating arcade of the hilar plate.